Rta-waṅ Dgā ldān rnām Rgyāl lhā rtseʼi bcaʼ yig mdor bsdus bʼzugs so - Ṅag-dbaṅ-rnam-rgyal, ʼPhyoṅ-rgyas-pa, 17th cent (Bsod grags podʼphren, 1979)
Monastic regulations of the Rta waṅ Monastery, in Arunachal Pradesh, India.